Oxalate formation under the hyperarid conditions of the Atacama desert as a mineral marker to provide clues to the source of organic carbon on Mars. Issue 6 (18th June 2016) - Cheng, Z. Y.; Fernández‐Remolar, D. C.; Izawa, M. R. M.; Applin, D. M.; Chong Díaz, M.; Fernandez‐Sampedro, M. T.; García‐Villadangos, M.; Huang, T.; Xiao, L.; Parro, V.
Abstract: In this study, we report the detection and characterization of the organic minerals weddellite (CaC2 O4 · 2H2 O) and whewellite (CaC2 O4 · H2 O) in the hyperarid, Mars‐like conditions of the Salar Grande, Atacama desert, Chile. Weddellite and whewellite are commonly of biological origin on Earth and have great potential for preserving records of carbon geochemistry and possible biological activity on Mars if they are present there. Weddellite and whewellite have been found as secondary minerals occurring inside the lower detrital unit that fills the Salar Grande basin. The extremely low solubility of most oxalate minerals inhibits detection of oxalate by ion chromatography (IC). Crystalline oxalates, including weddellite and whewellite, were detected by X‐ray diffraction (XRD). The association of weddellite with surface biota and its presence among subsurface detrital materials suggest the potential of a biological origin for Salar Grande weddellite and whewellite. In this regard, biological activity is uniquely capable of concentrating oxalates at levels detectable by XRD. The complementary detection of oxalate‐bearing phases through IC in the upper halite‐rich unit suggests the presence of a soluble oxalate phase in the basin that is not detected by XRD. The formation, transport, and concentration of oxalate in the Salar Grande may provide a geochemical analogue for oxalate‐bearing minerals recently suggested to exist on Mars. Key Points: Oxalate minerals were found in the hyperarid conditions of the Salar Grande basin, Atacama desert Biological versus abiotic pathways were recognized using mineral and geochemical techniques Such information can be used to reveal the origin of organic carbon on Mars